2007
DOI: 10.1111/j.1460-2695.2007.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the J integral fracture toughness of Al 6061 using the small punch test

Abstract: A B S T R A C TThe 6000 series aluminium alloys (Al-Mg-Si systems) are commonly used as mediumstrength structural materials; in particular, the 6061 (Al-1Mg-0.6Si) alloy is widely utilized as a general-purpose structural material due to its excellent formability and corrosionresisting capabilities. The objective of this study was to obtain a correlation between the small punch (SP) test estimated equivalent fracture strain (ε qf ) and fracture toughness (J 1C ) property for 6061 aluminium, and determine its vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Figure 5 shows a comparison of load -deflection curves obtained in the present study and the previous study [6]. From this figure, both results show fairly good agreement.…”
Section: Validity Of the Established Apparatussupporting
confidence: 72%
See 1 more Smart Citation
“…Figure 5 shows a comparison of load -deflection curves obtained in the present study and the previous study [6]. From this figure, both results show fairly good agreement.…”
Section: Validity Of the Established Apparatussupporting
confidence: 72%
“…To show validity of the manufactured SP testing apparatus, a quasi-static SP test using aluminum alloy 6061 is conducted at crosshead speed of 0.2 mm/min following the previous study [6]. Figure 5 shows a comparison of load -deflection curves obtained in the present study and the previous study [6].…”
Section: Validity Of the Established Apparatusmentioning
confidence: 99%
“…12(a) and (b), low and high magnification respectively. As continual straining of the material increases, the microvoids tend to grow, coalesce and eventually form an incessant fracture face [17,18]. Sample showed typical ductile failure occurred by formation of microvoids, void growth and finally coalescence.…”
Section: Failure Energy Of In-service Partsmentioning
confidence: 97%
“…This consists of the measurement of the so-called biaxial strain at fracture, e qf , which relates the original specimen thickness, t, to the thickness measured in the failure zone, t f (expression 1). Several authors [2,5,9,[11][12][13][14] have found good relationships between this parameter and fracture toughness, although very different, totally empirical expressions have been obtained, showing a clear dependence on the type of material. Other reported strategies include the measurement of the energy furnished by the test until a 20% drop after the application of the maximum load [6,15] or the estimation of the parameters of an appropriate damage model by applying neural networks to the SPT result and subsequently simulating the mechanical behaviour of the standard fracture toughness test [16,17].…”
Section: Introductionmentioning
confidence: 96%